The Prevalence of Left ventricular hypertrophy as a feature of Hypertensive Heart Disease in A Tertiary Hospital in Tanzania: An Echocardiographic Registry Study - Henry Anselmo Mayala; Delila Kimambo; Engerasiya Julius Kifai; Siza J Ngomero; Abuu Abdallah Dalidali; Paskal Elia Kondi; Gerson Imael Mpondo; Saada A Salum; Pedro Pallangyo; Mohamed Janabi (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Objective: Echocardiography is a useful noninvasive tool for the diagnosis and evaluation of cardiac diseases. This study aims to share our 3 months' experience in our echo lab as well as the scope of clinical cases diagnosed at our institute. Methods: This is a cross-sectional observational study conducted at the Jakaya Kikwete Cardiac Institute, in Dar-es-salaam, Tanzania between February 2020 to May 2020. This was performed with the Siemens Accuson S-300 machine using two dimensional, M-mode, colour flow and tissue Doppler protocols. Results: 1992 consecutive patients, 857 males and 1135 females, were examined during the study period. Their ages ranged from 27 to 84 years within a mean of 55±13 years. 1236 (62%) had left ventricular hypertrophy and diastolic dysfunction as features of hypertensive heart disease, 145 (7.2%) had dilated cardiomyopathy, 87 (4.4%) had ischemic cardiomyopathy, 54 (2.7%) had Rheumatic heart disease, also we had 450 (22.6%) who had a normal echo. Conclusion: Hypertensive heart disease was the immense echocardiographic diagnosis at our institute and is the most significant non-communicable diseases responsible for increased morbidity and mortality among our patients in Tanzania. Furthermore, a lot of effort needs to be done to increase awareness, prevention, treatment and drug compliance for hypertension to combat the complications.